The Growth of Seriatopora hystrix (Dana, 1846) Transplant with Differences of Fragments Size and Planting Position - Carissa Paresky Arisagy; Ratih Ida Adharini; Eko Setyobudi (Journal Omni-Akuatika, 2021)
Transplantation of coral reefs requires sufficient fragments but must still ensure the sustainability of coral donors. This research aimed to know the survival rate and growth rate of transplant corals with different fragment sizes and planting positions and to determine the most effective and efficient transplantation methods of the Seriatopora hystrix. The research was conducted from January to April 2016 in Serangan Island waters Denpasar Bali (1-2 m depth). The method used was a field experiment with variations of planting position (vertical, horizontal) and fragment sizes (3, 5, 7 cm). The results showed a high survival rate (98.3%) of the transplanted S. hystrix with planting position and fragment sizes variation. The variation of planting position and fragment sizes were significantly affected the length growth rate of the S. hystrix (p <0.05). The vertical planting position showed better growth compared to the horizontal planting position. The transplantation of coral with initial fragment sizes of 5 and 7 cm showed a higher growth rate than the fragment size of 3 cm. However, statistical analysis revealed no significant difference between initial fragment sizes of 5 and 7 cm. Therefore, this study demonstrated the most effective and efficient for S. hystrix transplantation showed in the vertical position with the initial fragment size of 5 cm.Key words: coral bleaching, initial fragment, tropical, zooxanthellae